Analisis Studi Kelayakan Bisnis: Pemasaran dan Manajaemen pada UMKM Keripik Cinta Mas Hendro - Gio Qaedy Auzan; Muttia Kartika; Tia Novira Sucipto; Widya Nizrina (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
The purpose of this study is to analyze the business feasibility study on MSME called Keripik Cinta Mas Hendro with marketing and management aspects. This study uses a descriptive qualitative method.  This research was conducted on an MSME called Keripik Cinta Mas Hendro. The data collection technique in this study uses interview and observation techniques. The data analysis technique in this study uses qualitative analysis. The results of this study show that: (1) Marketing Aspect, Keripik Cinta Mas Hendro focuses on marketing by offering good quality products at affordable prices. They distribute their products widely within the city, clearly targeting a specific group of customers. Cinta Mas Hendro chips are made in many shops in Secanggang. (2) Management aspect, where it is clear who is responsible for planning, supervising, and providing Standard Operating Procedures (SOPs) to employees to distribute Cinta Mas Hendro Chips. Judging from the marketing aspect in the sales target and marketing mix, the management aspect is organized with a manager who plans and implements.